A lithium metal negative electrode current collector and preparation method thereof, and a lithium metal battery

By using oxygen plasma treatment and hydrothermal method on the lithium metal negative electrode, the GZnO/CC current collector prepared from bottom to top is achieved, the problem of lithium dendrites is solved, and the cycle stability and energy density of the battery are improved.

CN119481083BActive Publication Date: 2025-04-08HUNAN JAPRUI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510053304.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Lithium metal negative electrodes are prone to dendrites, resulting in short circuits and safety hazards. At the same time, the existing 3D metal-based skeleton current collectors lead to an increase in the battery mass and reduce the mass energy density.

Method used

Through single-sided oxygen plasma treatment and one-step hydrothermal method, a three-dimensional carbon cloth current collector (GZnO/CC) with a longitudinal zinc oxide gradient distribution was prepared. The current collector achieved uniform deposition from bottom to top on the lithium metal negative electrode to inhibit the formation of dendrites.

Benefits of technology

The electrode cycle stability is improved, the high energy density and long cycle life of lithium metal batteries are achieved, and the formation of lithium dendrites is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481083B_ABST
    Figure CN119481083B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium metal negative electrode current collector and a preparation method thereof, and a lithium metal battery. The method comprises: treating a carbon cloth on one side in oxygen plasma for 8-12 seconds to obtain a carbon cloth with gradient activation; dissolving Zn(NO3)2 and urotropine in water, slowly adding ammonia water, and obtaining a colorless and transparent precursor solution; transferring the precursor solution to a polytetrafluoroethylene liner, hydrothermally reacting with the carbon cloth with gradient activation, cooling to room temperature, washing and drying to obtain the lithium metal negative electrode current collector. The present invention obtains a three-dimensional carbon cloth current collector with a longitudinal zinc oxide gradient distribution by single-sided oxygen plasma treatment and a one-step hydrothermal method, and at the same time, by effectively controlling the concentration distribution of ZnO, induces lithium to deposit from bottom to top and grow uniformly in a three-dimensional carbon cloth skeleton with a gradient distribution of ZnO lithium-philic sites, inhibits the formation of lithium dendrites, improves the electrode cycle stability, and achieves long cycle stability and high energy density of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery current collectors, in particular to a lithium metal negative electrode current collector and a preparation method thereof, and a lithium metal battery. Background Art

[0002] The excellent theoretical capacity of lithium metal anode (3860 mAh g -1 ) and the lowest redox potential (-3.04 V, compared with the standard hydrogen electrode) are considered to be the preferred material to replace commercial graphite anodes. However, the lowest redox potential possessed by lithium metal is a double-edged sword. In addition to obtaining a higher output voltage, it also intensifies the side reactions between the lithium metal anode and the electrolyte. In addition to the infinite volume change and continuous internal stress fluctuations, it is also challenging to achieve the passivation of the lithium metal anode, which may affect the consumption of lithium and the subsequent lithium deposition behavior. Weak Li-Li bonds make lithium metal deposition more prone to dendrites, which can easily cause short circuits and pose serious safety hazards.

[0003] Copper foil is a traditional substrate material, but its low specific surface area and lithium repellency lead to serious uneven growth of lithium during deposition / stripping, which easily induces lithium dendrites. In addition, the existing 3D commercial metal-based skeleton current collector will increase the mass of the overall battery, thereby significantly reducing the mass energy density of the battery.

[0004] Therefore, the industry urgently needs a new technology for lithium metal negative electrode current collector. Summary of the invention

[0005] In order to solve the technical problem that lithium metal deposition in the existing lithium metal negative electrode is more likely to produce dendrites and easily cause short circuits, the present invention provides a lithium metal negative electrode current collector and a preparation method thereof, and obtains a three-dimensional carbon cloth current collector (GZnO / CC) with a longitudinal zinc oxide gradient distribution through a single-sided oxygen plasma treatment that is easy to control and a one-step hydrothermal method. The present invention effectively controls the concentration distribution of ZnO, induces lithium to deposit from bottom to top and grow uniformly in the three-dimensional carbon cloth skeleton with a gradient distribution of ZnO lithium-philic sites, inhibits the formation of lithium dendrites, thereby improving the electrode cycle stability and fully realizing the high energy density of lithium metal batteries.

[0006] To achieve the above object, the present invention provides a method for preparing a lithium metal negative electrode current collector, comprising the following steps:

[0007] Step 1: treating the carbon cloth on one side in oxygen plasma to obtain a carbon cloth with gradient activation;

[0008] Step 2: Dissolve Zn(NO3)2 and urotropine in water, slowly add ammonia water to obtain a colorless and transparent precursor solution;

[0009] Step 3: transfer the precursor solution obtained in step 2 into a polytetrafluoroethylene liner, add the gradient activated carbon cloth in step 1, perform a hydrothermal reaction, cool to room temperature, wash and dry, and obtain the lithium metal negative electrode current collector GZnO / CC.

[0010] Furthermore, before step 1, the carbon cloth is pretreated, specifically, the carbon cloth is soaked in 0.5-2M hydrochloric acid for 10-15 hours, and then the carbon cloth is washed with anhydrous ethanol and deionized water for multiple times and vacuum dried.

[0011] Furthermore, in step 1, the thickness of the carbon cloth is 0.3-0.4 mm, and the time for single-side treatment of the carbon cloth in oxygen plasma is 8-12 seconds.

[0012] Furthermore, in step 2, the mass ratio of Zn(NO3)2 and urotropine is 2-2.2:1; and 0.5-2 mL of aqueous ammonia is added for every 0.19 g of Zn(NO3)2.

[0013] Furthermore, in step three, the temperature of the hydrothermal reaction is 105-125° C., and the time is 20-24 hours.

[0014] Furthermore, in step three, after the hydrothermal reaction, washing and drying are performed, specifically, washing the sample with ethanol and deionized water and then drying it at 50-70°C.

[0015] Furthermore, the method further comprises post-processing the obtained GZnO / CC: placing the obtained GZnO / CC into an ethanol solution containing tetrabutyl titanate, soaking it, and then drying it.

[0016] The present invention also provides a lithium metal negative electrode current collector, which is prepared by using the above-mentioned method for preparing a lithium metal negative electrode current collector.

[0017] The present invention also provides a lithium metal battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode adopts the above-mentioned current collector deposited with lithium metal, and the positive electrode adopts LiFePO4.

[0018] The present invention also provides a method for preparing the above-mentioned lithium metal battery, firstly punching the above-mentioned current collector into pole pieces, using lithium sheets as counter electrodes, and assembling the battery using a diaphragm and an electrolyte, wherein the side not treated by oxygen plasma is placed close to the lithium counter electrode, and then lithium deposition is performed; after the lithium metal is deposited on the current collector, the battery is disassembled, the current collector with deposited lithium metal is taken out as the negative electrode, the LiFePO4 material is taken out as the positive electrode, and the battery is reassembled using a new diaphragm and an electrolyte to obtain a lithium metal battery product.

[0019] The present invention has the following beneficial effects:

[0020] 1. The present invention provides a method for preparing a lithium metal negative electrode current collector, wherein the carbon cloth is first treated on one side in oxygen plasma to obtain a gradient activated carbon cloth; Zn(NO3)2 and urotropine are then dissolved in water, and ammonia water is slowly added to obtain a colorless and transparent precursor solution; the precursor solution is finally transferred to a polytetrafluoroethylene liner, and the gradient activated carbon cloth is added to perform a hydrothermal reaction, and after cooling to room temperature, the mixture is washed and dried to obtain the lithium metal negative electrode current collector GZnO / CC. The lithium metal negative electrode current collector prepared by the present invention is a carbon cloth current collector modified by ZnO nanoflowers with gradient lithium affinity, and the obtained gradient GZnO / CC current collector has excellent electrochemical properties. This is because in the present invention, one side of the carbon cloth is treated with an oxygen plasma treatment apparatus for a short period of time with medium intensity, and only one side of the carbon cloth is given active oxygen functional groups (such as -OH, -COOH and -CHO, etc.), thereby obtaining different degrees of hydrophilicity, and the hydrophilicity will affect the active sites of the hydrothermal reaction, so that more ZnO will be deposited on the side with stronger hydrophilicity, thereby achieving its gradient lithium affinity. Due to the gradient distribution characteristics of ZnO active sites in GZnO / CC, the diffusion dynamics of lithium ions are improved, and lithium ions tend to be deposited in the lower part of the current collector with higher density of ZnO active sites and stronger lithium affinity. The gradient distribution of lithium-affinity sites optimizes the lithium deposition behavior, allowing lithium to grow uniformly and densely throughout the carbon cloth skeleton, effectively solving the growth of lithium dendrites.

[0021] In addition, the synergistic protonation of the amine groups of the urotropine solution itself or its hydrolysis accelerates the Zn 2+ The hydrolysis of urotropine promotes the growth of ZnO. Hexamethylenetetramine hydrolyzes into aldehydes and amines, of which the amines form a stable and controllable pH buffer system and provide OH- groups when forming ammonium hydroxyl compounds. Zn 2+ Will be with (NH4) + , (CH2)6N4, OH- form some active substances. Zinc will form complexes with hydroxyl groups, and the ZnO crystal nucleus will gradually grow with the condensation of the surface of these complexes.

[0022] 2. The gradient lithium affinity of the lithium metal negative electrode current collector prepared by the present invention ensures that lithium deposition is exhibited from bottom to top on the GZnO / CC current collector in the symmetrical battery, and can maximize the characteristics of the three-dimensional carbon cloth current collector in reducing the local current density, ensuring that the symmetrical battery made of GZnO / CC can deposit / strip lithium metal more uniformly, effectively inhibit the formation of lithium dendrites, and achieve the lowest voltage polarization and the longest cycle life. The three-dimensional conductive framework of the carbon cloth current collector in the present invention effectively inhibits the volume expansion of lithium metal and the formation of lithium dendrites, so that the deposition behavior of lithium on GZnO / CC is manifested as uniform growth from bottom to top in the current collector phase. The gradient lithium affinity three-dimensional carbon cloth current collector prepared by the present invention enhances the conductivity of the electrode and effectively alleviates the growth of lithium dendrites during the lithium storage process, so that the lithium ion full battery using the gradient current collector prepared by the present invention as the negative electrode achieves high specific capacity and cycle stability.

[0023] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0025] Figure 1 This is the XRD diagram of the GZnO / CC material obtained in the first preferred embodiment of the present invention;

[0026] Figure 2 is a SEM image of the GZnO / CC material obtained in the first preferred embodiment of the present invention; wherein, Figure 2 (a) is a scanning electron microscope image of the cross section of GZnO / CC along the gradient direction; (b) is the surface morphology of the carbon cloth on the untreated side; (c) is the surface morphology of the carbon cloth on the oxygen plasma treated side;

[0027] Figure 3 Schematic diagram of the contact angle of the carbon cloth after oxygen plasma treatment obtained in the first preferred embodiment of the present invention; wherein, Figure 3 (a) is a schematic diagram of the contact angle of one side of the carbon cloth treated with oxygen plasma, and (b) is a schematic diagram of the contact angle of the other side of the carbon cloth not treated with oxygen plasma;

[0028] Figure 4 This is the symmetric battery test result of the GZnO / CC material obtained in the preferred embodiment 1 of the present invention;

[0029] Figure 5 At a current density of 1 mA cm -2When 12 mAh cm was deposited on the GZnO / CC current collector obtained in the preferred embodiment 1 of the present invention and the comparative examples 1 and 2, -2 A cross-sectional view of lithium; wherein, Figure 5 (a) is a cross-sectional view of Example 1; (b) is a cross-sectional view of Comparative Example 1; (c) is a cross-sectional view of Comparative Example 2;

[0030] Figure 6 It is a schematic diagram of a long cycle of a full battery at 1C, using the current collectors obtained in Example 1, Comparative Example 1 and Comparative Example 2 after pre-lithiation as the negative electrode and LiFePO4 as the positive electrode;

[0031] Figure 7 The schematic diagram of rate cycling of a full battery at different current densities is respectively based on the current collector obtained in Example 1, Comparative Example 1 and Comparative Example 2 after pre-lithiation as the negative electrode and LiFePO4 as the positive electrode. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Using three-dimensional materials as current collectors not only provides sufficient buffer space for lithium metal deposition and alleviates volume expansion, but also enhances the electron transport capacity of the electrode, reduces local current density, and significantly improves the electrochemical performance of lithium metal batteries. Secondly, by adjusting the gradient of the current collector's conductivity and lithium affinity, lithium is induced to grow uniformly from bottom to top on the three-dimensional current collector, effectively inhibiting the generation of lithium dendrites. The present invention obtains a three-dimensional carbon cloth current collector (GZnO / CC) with a longitudinal zinc oxide gradient distribution through a single-sided oxygen plasma treatment and a one-step hydrothermal method that is easy to control. By effectively controlling the concentration distribution of ZnO, lithium is induced to deposit and grow uniformly from bottom to top in the three-dimensional carbon cloth skeleton with a gradient distribution of ZnO lithium affinity sites, inhibiting the formation of lithium dendrites, thereby improving the electrode cycle stability and fully realizing the high specific capacity and long cycle stability of lithium metal batteries.

[0034] Embodiment 1:

[0035] A method for preparing a lithium metal negative electrode current collector comprises the following steps:

[0036] Part 1: Carbon cloth pretreatment:

[0037] The first step is to soak the carbon cloth in 1M hydrochloric acid for 12 h, then wash the commercial carbon cloth with anhydrous ethanol and deionized water for multiple times and vacuum dry it;

[0038] The second step is to treat the dried carbon cloth on one side in oxygen plasma for 12 seconds to obtain a carbon cloth with gradient activation;

[0039] Part 2: Using the pretreated carbon cloth as the substrate, a three-dimensional carbon cloth current collector (GZnO / CC) with a longitudinal zinc oxide content gradient distribution was prepared by a hydrothermal method:

[0040] Step 1: Dissolve 0.19 g Zn(NO3)2 and 0.091 g urotropine in 40 mL deionized water, slowly add 1 mL ammonia water, and stir at room temperature for 20 min to obtain a colorless and transparent solution;

[0041] The second step is to transfer the precursor solution to the polytetrafluoroethylene liner for hydrothermal reaction, and vertically add a piece of single-sided activated carbon cloth (4 cm×4 cm). At this time, it can be clearly observed that the hydrophilicity and hydrophobicity of the two sides of the carbon cloth are different in the polytetrafluoroethylene liner. The hydrophilic side is completely infiltrated, while the hydrophobic side cannot be completely infiltrated in a short time.

[0042] The third step is to perform a hydrothermal reaction in a forced air drying oven with the temperature set at 105 °C and continue the treatment for 24 hours. After naturally cooling to room temperature, the sample is washed with ethanol and deionized water and dried at 60 °C to obtain GZnO / CC.

[0043] Embodiment 2:

[0044] A method for preparing a lithium metal negative electrode current collector comprises the following steps:

[0045] Part 1: Carbon cloth pretreatment:

[0046] The first step is to soak the carbon cloth in 1M hydrochloric acid for 12 h, then wash the commercial carbon cloth with anhydrous ethanol and deionized water for multiple times and vacuum dry it;

[0047] The second step is to treat the dried carbon cloth in oxygen plasma for 10 seconds on one side to obtain a carbon cloth with gradient activation on one side;

[0048] Part 2: Using the pretreated carbon cloth as the substrate, a three-dimensional carbon cloth current collector (GZnO / CC) with a longitudinal zinc oxide content gradient distribution was prepared by a hydrothermal method:

[0049] Step 1: Dissolve 0.364 g Zn(NO3)2 and 0.182 g urotropine in 40 mL deionized water, slowly add 2 mL ammonia water, and stir at room temperature for 20 min to obtain a colorless and transparent solution;

[0050] The second step is to transfer the precursor solution to the polytetrafluoroethylene liner for hydrothermal reaction, and vertically add a piece of single-sided activated carbon cloth (4 cm×4 cm). At this time, it can be clearly observed that the hydrophilicity and hydrophobicity of the two sides of the carbon cloth are different in the polytetrafluoroethylene liner. The hydrophilic side is completely infiltrated, while the hydrophobic side cannot be completely infiltrated in a short time.

[0051] The third step is to perform a hydrothermal reaction in a forced air drying oven with the temperature set at 110 °C and continue the treatment for 22 hours. After naturally cooling to room temperature, the sample is washed with ethanol and deionized water and dried at 50 °C to obtain GZnO / CC.

[0052] Embodiment three:

[0053] A method for preparing a lithium metal negative electrode current collector comprises the following steps:

[0054] Part 1: Carbon cloth pretreatment:

[0055] The first step is to soak the carbon cloth in 1M hydrochloric acid for 12 h, then wash the commercial carbon cloth with anhydrous ethanol and deionized water for multiple times and vacuum dry it;

[0056] Step 2: Treat the dried carbon cloth in oxygen plasma for 8 seconds on one side to obtain a carbon cloth with gradient activation on one side;

[0057] Part 2: Using the pretreated carbon cloth as the substrate, a three-dimensional carbon cloth current collector (GZnO / CC) with a longitudinal zinc oxide content gradient distribution was prepared by a hydrothermal method:

[0058] In the first step, 0.2 g Zn(NO3)2 and 0.091 g urotropine were dissolved in 40 mL deionized water, 1 mL ammonia water was slowly added, and stirred at room temperature for 20 min to obtain a colorless and transparent solution.

[0059] In the second step, the precursor solution is transferred to the polytetrafluoroethylene liner where the hydrothermal reaction is carried out, and a piece of single-sided activated carbon cloth (4 cm×4 cm) is vertically added. At this time, the different hydrophilicity and hydrophobicity of the two sides of the carbon cloth can be clearly observed in the polytetrafluoroethylene liner. The hydrophilic side is completely soaked, while the hydrophobic side cannot be completely soaked in a short time.

[0060] The third step is to perform a hydrothermal reaction in a forced air drying oven, set the temperature to 125 °C, and continue the treatment for 20 hours. After cooling naturally to room temperature, the sample is washed with ethanol and deionized water and dried at 70 °C to obtain GZnO / CC.

[0061] Embodiment 4:

[0062] The difference between Example 4 and Example 1 is that the obtained GZnO / CC is post-treated; the obtained GZnO / CC is placed in an ethanol solution containing 0.1 mol / L tetrabutyl titanate, soaked for 24 hours, taken out, and dried at 80°C for 12 hours to decompose the tetrabutyl titanate and form a layer of TiO2 nanoparticles on the surface of the GZnO / CC, thereby obtaining the modified GZnO / CC.

[0063] Comparative Example 1:

[0064] The difference between Comparative Example 1 and Example 1 is that in the second step of the first part, the carbon cloth is not treated with plasma, so that ZnO grows uniformly on the carbon cloth, and the other steps are the same as Example 1.

[0065] Comparative Example 2:

[0066] The difference between Comparative Example 2 and Example 1 is that the first part is not subjected to plasma treatment, and the second part is not subjected to ZnO loading on the carbon cloth, that is, pure carbon cloth.

[0067] Comparative Example 3:

[0068] The difference between Comparative Example 3 and Example 1 is that in the first step of the second part, 1.9 g Zn(NO3)2 and 0.91 g urotropine are dissolved in 40 mL deionized water, and 10 mL ammonia water is slowly added. The other steps are the same as in Example 1.

[0069] Comparative Example 4:

[0070] The difference between Comparative Example 4 and Example 1 is that in the second step of the first part, the carbon cloth is treated with oxygen plasma for 20 seconds, and the other steps are the same as those of Example 1.

[0071] Comparative Example 5:

[0072] The difference between Comparative Example 5 and Example 1 is that in the third step of the second part, the hydrothermal temperature is set to 90° C., and the other steps are the same as Example 1.

[0073] The GZnO / CC material obtained in Example 1 was subjected to X-ray diffraction (XRD) testing to obtain the following XRD images: Figure 1 As shown. Figure 1 It can be seen that the GZnO / CC current collectors all show clear ZnO characteristic peaks, which is consistent with the results of the standard card PDF # 99-0111, proving that ZnO is effectively synthesized on the carbon cloth current collector. On the other hand, GZnO / CC still maintains the characteristic peaks of carbon elements, indicating that oxygen plasma treatment and hydrothermal reaction do not destroy the carbon cloth skeleton and generate other interfering impurities.

[0074] The GZnO / CC material obtained in Example 1 was tested by scanning electron microscopy (SEM), and the following SEM images were obtained: Figure 2 As shown, Figure 2 (a) is a scanning electron microscope image of the cross section of GZnO / CC along the gradient direction (the upper part of the current collector is the carbon cloth on the side not treated by oxygen plasma, and the lower part is the carbon cloth on the side treated by oxygen plasma); (b) is the surface morphology of the carbon cloth on the side not treated by oxygen plasma; (c) is the surface morphology of the carbon cloth on the side treated by oxygen plasma. Figure 2 It can be seen that GZno / CC presents different concentration gradients of ZnO deposition in the vertical direction of the carbon cloth. The surface of the untreated carbon cloth of GZnO / CC is smooth, without obvious surface modification or deposition of active substances. The carbon cloth on the plasma-treated side is fully grown with ZnO nanoflowers, with unique active site modifications of different degrees.

[0075] Figure 3 Schematic diagram of the contact angle of the carbon cloth after plasma treatment obtained in the first preferred embodiment of the present invention, wherein: Figure 3 (a) is a schematic diagram of the contact angle of one side of the carbon cloth after being treated with oxygen plasma. Figure 3 (b) is a schematic diagram of the contact angle of the other side of the carbon cloth that has not been treated with oxygen plasma. Figure 3 The contact angle test shows that the contact angle of the side directly treated with oxygen plasma is significantly smaller than that of the other side, proving that there is a significant difference in the hydrophilicity of the two sides of the carbon cloth. One side of the carbon cloth was treated with a medium-intensity oxygen plasma treatment apparatus for a short time. Plasma treatment can give active oxygen functional groups (such as -OH, -COOH and -CHO, etc.) to one side of the carbon cloth, thereby obtaining different degrees of hydrophilicity. Hydrophilicity affects the active sites of the hydrothermal reaction, so that more ZnO will be deposited on the more hydrophilic side.

[0076] The current collectors prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were subjected to symmetric battery performance tests, specifically:

[0077] In the first step, the button cell was assembled in a glove box filled with Ar atmosphere (H2O < 0.5 ppm, O2 < 0.5 ppm). 1 M LiTFSI + DOL / DME (v:v = 1:1) + 2 wt% LiNO3 was used as the electrolyte of the battery, GZnO / CC was used as the electrode (the side not treated by plasma was facing the lithium metal counter electrode), and the lithium sheet was used as the counter electrode to assemble the button cell. 105 µL of electrolyte solution was added to each button cell.

[0078] The second step is to place the assembled battery on the electrochemical test channel at 1 mA h -2The current density was deposited for 12 h, so that 12 mAh cm was pre-deposited on the GZnO / CC current collector. -2 of lithium metal.

[0079] The third step is to test the symmetrical battery with a certain current density on the GZnO / CC current collector after the deposition.

[0080] The full battery test was then carried out, specifically: first using commercial LiFePO4 (LFP) as the positive electrode, 4 mAh cm -2 The Li@GZnO / CC current collector after lithium pre-deposition is used as the negative electrode for full battery matching, and the loading amount of the positive electrode material is about 8 mg cm -2 The capacity ratio of the negative electrode to the positive electrode is about 1.8-2. The assembled full battery is then subjected to charge and discharge cycle tests and rate performance tests under a voltage window of 2.8-3.9 V.

[0081] The GZnO / CC current collector prepared in Example 1 has a -2 The current density and 1 mAh cm -2 Under the capacity of , the symmetrical battery test results are as follows Figure 4 shown. Figure 4 The symmetric battery test results in the paper show that the concentration gradient design of lithiophilic ZnO can make lithium metal deposit from bottom to top, which can maximize the characteristics of three-dimensional carbon cloth current collector to reduce local current density, ensuring that the symmetric battery of GZnO / CC can deposit / strip lithium metal more evenly and effectively inhibit the formation of lithium dendrites. Because the deposition mode and direction of lithium have changed, it starts to deposit from the bottom, leaving space for the upper layer to deposit evenly, making the symmetric battery more stable at 1mA cm -2 The current density and 1 mAh cm -2 At a capacity density of 1.34 W, the GZnO / CC current collector exhibits an ultra-long lifespan of 2500 h and a low voltage polarization of 14 mV.

[0082] Figure 5 The current density is 1 mA cm -2 When 12 mAh cm was deposited on the GZnO / CC current collector obtained in Example 1 and Comparative Examples 1 and 2, -2 A cross-sectional view of lithium. Figure 5It can be seen that in Example 1, due to the gradient distribution characteristics of ZnO active sites in GZnO / CC, the diffusion dynamics of lithium ions are improved, and lithium ions tend to be deposited in the lower part of the current collector (i.e., the side of the carbon cloth treated with oxygen plasma) where the density of ZnO active sites is higher and the lithium affinity is stronger. The gradient distribution of lithium-affinity sites optimizes the lithium deposition behavior, allowing lithium to grow evenly and densely throughout the carbon cloth skeleton, effectively solving the growth of lithium dendrites. Although the uniform concentration of ZnO in Comparative Example 1 increases the lithium affinity of the carbon cloth current collector, the uniformly distributed zinc oxide cannot adjust the lithium deposition method. The characteristic of lithium preferentially depositing on the upper surface makes it easy to grow lithium dendrites or even dead lithium. In Comparative Example 2, due to the lack of lithium-affinity sites in pure carbon cloth, the lithium in the carbon cloth current collector is randomly deposited and grown on the carbon skeleton, resulting in a large amount of space at the bottom of the carbon cloth not being utilized and severe growth of lithium dendrites.

[0083] Figure 6 The long cycle comparison chart of the full battery at 1C is respectively using the current collector obtained in Example 1 after pre-lithiation (i.e., carbon cloth current collector with lithium metal deposited) and Comparative Examples 1 and 2 as the negative electrode and LiFePO4 as the positive electrode. Figure 6 It can be seen that the lithium affinity gradient design in Example 1 solves the problem of lithium dendrite growth in the full battery cycle and achieves stability under long cycles. However, the uniform ZnO in Comparative Example 1 cannot avoid lithium dendrite growth and thus has poor cycle performance. In Comparative Example 2, the generation of dead lithium in the negative electrode of pure carbon cloth causes the full battery capacity to suddenly decay.

[0084] Figure 7 The figure is a schematic diagram of the rate cycle of a full battery at different current densities, using the current collectors obtained in Example 1 and Comparative Example 1 and Comparative Example 2 after pre-lithiation as the negative electrode and LiFePO4 as the positive electrode. Figure 7 It can be seen that the lithium affinity gradient design in Example 1 solves the problem of lithium dendrite growth in the full battery cycle, increases the conductivity of the electrode, and achieves high rate performance of the full battery. However, the uniform ZnO in Comparative Example 1 cannot avoid the growth of lithium dendrites, so it shows poor specific capacity at high current density. In Comparative Example 2, the generation of dead lithium in the negative electrode of pure carbon cloth and poor conductivity make the full battery rate performance extremely poor.

[0085] Table 1 shows the full cell performance results of Li@GZnO / CC||LFP at 1C rate for batteries assembled with current collectors prepared in Examples 1 to 4 and Comparative Examples 1 to 5.

[0086] Table 1:

[0087]

[0088] Depend on Figure 6 and Figure 7As shown in Table 1, the lithium-ion full battery with the current collector prepared in the embodiment of the present invention as the negative electrode has achieved high specific capacity and cycle stability. In particular, under the condition of charge and discharge rate of 1 C, the Li@GZnO / CC||LFP full battery in Example 1 can stably operate for 1000 cycles and still maintain 135 mAh g -1 The ultra-high capacity has a capacity retention rate of up to 90.7%. The gradient lithium-philic three-dimensional carbon cloth current collector prepared by the present invention enhances the conductivity of the electrode and effectively alleviates the growth of lithium dendrites during the lithium storage process, thereby reducing lithium loss and reducing irreversible capacity loss. In comparative example 1, due to the uniform particle concentration of ZnO, the dendrite growth and the generation of dead lithium during the lithium storage process cannot be avoided, resulting in a certain degree of lithium loss. In comparative example 2, the poor conductivity of pure carbon cloth and the extremely uneven lithium growth lead to poor cycle performance. In comparative examples 3 and 4, due to the increase in the concentration of the precursor solution or the long plasma treatment time, the surface of the carbon cloth does not generate gradient-distributed ZnO particle growth. Therefore, lithium deposition cannot be performed from bottom to top during the lithium storage process, so the dendrite growth makes the full battery cycle performance poor. In comparative example 5, due to the low hydrothermal temperature, lithium-philic ZnO cannot be formed. Therefore, its uneven lithium growth causes poor cycle stability.

[0089] Example 4 introduces TiO2, which has a high theoretical specific capacity and good chemical stability. Its nanoparticle layer can increase the specific surface area of ​​GZnO / CC and provide more lithium ion storage sites. At the same time, TiO2 can also improve the conductivity of the electrode material and the diffusion kinetics of lithium ions, thereby improving the charge and discharge performance and specific capacity of the battery. There is structural synergy between TiO2 and GZnO / CC. TiO2 fills the pores and protects the internal structure. The two provide each other with attachment and diffusion channels; electronic conduction synergy, electrons transfer between the two, reduce transfer resistance, and improve conduction efficiency; lithium ion diffusion synergy, GZnO / CC provides macroscopic channels, TiO2 provides microscopic sites, reduces diffusion resistance, and multiple synergistic effects improve the electrochemical performance and specific capacity of the battery. However, this solution increases the specific capacity but reduces the capacity retention rate, mainly because the structural stability is destroyed, poor interface bonding leads to side reactions, affecting lithium ion transmission and active substances; electrolyte decomposition and active substance dissolution trigger electrochemical side reactions; lithium ion diffusion path and kinetic performance are poor, high-rate charging and discharging as well as overcharging and over-discharging aggravate polarization and material degradation, which together lead to increased capacity attenuation and reduced retention rate.

[0090] In summary, the present invention provides a method for preparing a lithium metal negative electrode current collector, wherein the carbon cloth is first treated on one side in oxygen plasma to obtain a gradient activated carbon cloth; Zn(NO3)2 and urotropine are then dissolved in water, and ammonia water is slowly added to obtain a colorless and transparent precursor solution; finally, the precursor solution is transferred to a polytetrafluoroethylene liner, and a carbon cloth with one side surface activated is added to perform a hydrothermal reaction, and after cooling to room temperature, the lithium metal negative electrode current collector GZnO / CC is obtained by washing and drying. The lithium metal negative electrode current collector prepared by the present invention is a carbon cloth current collector modified by ZnO nanoflowers with gradient lithium affinity, and the obtained gradient GZnO / CC current collector has excellent electrochemical properties. This is because in the present invention, one side of the carbon cloth is treated with an oxygen plasma treatment apparatus for a short period of time with medium intensity, and only one side of the carbon cloth is given active oxygen functional groups (such as -OH, -COOH and -CHO, etc.), thereby obtaining different degrees of hydrophilicity, and the hydrophilicity will affect the active sites of the hydrothermal reaction, so that more ZnO will be deposited on the side with stronger hydrophilicity, thereby achieving its gradient lithium affinity. Due to the gradient distribution characteristics of ZnO active sites in GZnO / CC, the diffusion dynamics of lithium ions are improved, and lithium ions tend to be deposited in the lower part of the current collector with higher density of ZnO active sites and stronger lithium affinity. The gradient distribution of lithium-affinity sites optimizes the lithium deposition behavior, allowing lithium to grow uniformly and densely from bottom to top in the entire carbon cloth skeleton, effectively solving the growth of lithium dendrites. The present invention obtains a three-dimensional carbon cloth current collector with a longitudinal zinc oxide gradient distribution through an easily controllable single-sided oxygen plasma treatment and a one-step hydrothermal method. At the same time, by effectively controlling the concentration distribution of ZnO, lithium is induced to deposit and grow uniformly from bottom to top in a three-dimensional carbon cloth skeleton with a gradient distribution of ZnO lithium-philic sites, thereby inhibiting the formation of lithium dendrites in lithium metal batteries and improving the electrode cycle stability to fully realize the long cycle stability and high energy density of lithium full batteries.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium metal negative electrode, characterized in that: The following steps are involved: Step 1: treating the carbon cloth on one side in oxygen plasma to obtain a carbon cloth with gradient activation; Step 2: Dissolve Zn(NO3)2 and urotropine in water, slowly add ammonia water to obtain a colorless and transparent precursor solution; Step 3: Transfer the precursor solution obtained in step 2 to a polytetrafluoroethylene liner, and vertically add the gradient activated carbon cloth in step 1 to perform a hydrothermal reaction. After cooling to room temperature, wash and dry to obtain a three-dimensional carbon cloth current collector GZnO / CC with a zinc oxide gradient distribution. Step 4: punching the current collector obtained in step 3 into a pole piece, using a lithium sheet as a counter electrode, and assembling a battery using a diaphragm and an electrolyte, wherein the side not treated by oxygen plasma is close to the lithium counter electrode, and then lithium deposition is performed; when the lithium metal is deposited on the current collector, the battery is disassembled, and the current collector with the deposited lithium metal is taken out, which is the lithium metal negative electrode; Wherein, in step 1, the thickness of the carbon cloth is 0.3-0.4 mm, and the time for single-side treatment of the carbon cloth in oxygen plasma is 8-12 seconds; In step 2, the mass ratio of Zn(NO3)2 to urotropine is 2-2.2:1; 0.5-2 mL of ammonia water is added for every 0.19 g of Zn(NO3)2; In step 3, the temperature of the hydrothermal reaction is 105-125° C. and the time is 20-24 hours.

2. The method for preparing a lithium metal negative electrode according to claim 1, characterized in that: Before step 1, the carbon cloth is also pretreated, specifically, the carbon cloth is soaked in 0.5-2M hydrochloric acid for 10-15 hours, and then the carbon cloth is washed with anhydrous ethanol and deionized water for multiple times and vacuum dried.

3. The method for preparing a lithium metal negative electrode according to claim 1, characterized in that: In step three, after the hydrothermal reaction, the sample is washed and dried, specifically, the sample is washed with ethanol and deionized water and then dried at 50-70°C.

4. The method for preparing a lithium metal negative electrode according to claim 1, characterized in that: The method also includes post-processing the obtained GZnO / CC: placing the obtained GZnO / CC into an ethanol solution containing tetrabutyl titanate, soaking it, and then drying it.

5. A lithium metal negative electrode, characterized in that The lithium metal negative electrode is prepared by the method for preparing a lithium metal negative electrode according to any one of claims 1 to 4.

6. A lithium metal battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The negative electrode is the lithium metal negative electrode as claimed in claim 5, and the positive electrode is LiFePO4.

Citation Information

Patent Citations

  • Preparation method and application of composite electrode material for inhibiting growth of lithium dendrites

    CN113823795A

  • Composite metal lithium negative electrode, preparation method thereof, lithium secondary battery and device

    CN115461891A